Depressive disorders in children and infants - Boucherit , Saci (Journal of Human Sciences, 2020)
Depressive disorder in prepubertal children has long been ignored and the clinical reality of this pathology was not recognized until the 1970s. Indeed, until this date, several authors maintain that depression disease did not exist in children due to the incomplete maturation of psychic instances. On the other hand, the concept of "depressive position" as a fundamental and normal stage of the child's development was the subject of a rich theoretical elaboration, in the first half of the 20th Century. In addition, the effects of separation in the newborn and the child were studied, and the existence of clinical suffering was recognized.